(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article provides an in-depth analysis of the role and importance of informal education in developing the advanced pedagogical competencies of school teachers. Considering that traditional professional development systems cannot fully meet the demands of the times, international best practices and recent reforms in Uzbekistan were compared. The study reveals the proven advantages of innovative mechanisms such as Professional Learning Communities (PLCs), reverse mentoring, and digital microlearning. In conclusion, clear recommendations have been developed on the strategic directions for independent, free, and continuous professional development to provide targeted support for teachers.